ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH IMPLEMENTASI PSAK 115: STUDI KASUS KOMPARATIF PADA PT AGUNG PODOMORO LAND TBK DAN PT SUMMARECON AGUNG TBK - Novia Nabila Tulrahmi; Ilham illahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the impact of the implementation of PSAK 115 on the financial performance of PT Agung Podomoro Land Tbk (APLN) and PT Summarecon Agung Tbk (SMRA) using a comparative case study approach. The study employs a descriptive qualitative method involving document analysis of financial statements and Notes to the Financial Statements (CALK) for the 2019–2024 period. The analysis focuses on changes in revenue recognition policies, changes in the presentation of financial statement accounts, and their impact on the Return on Assets (ROA), Return on Equity (ROE), Debt-to-Assets Ratio (DAR), and Debt-to-Equity Ratio (DER). The results of the study show that the implementation of PSAK 115 changed the revenue recognition mechanism from a percentage-of-completion approach to a performance obligation approach. This change resulted in adjustments to revenue, contract liabilities, and retained earnings, particularly during the initial phase of implementation. The impact of PSAK 115’s implementation differed between the two companies. APLN exhibited greater fluctuations in financial performance due to the nature of its apartment and commercial property projects, which are highly dependent on the timing of unit handover. In contrast, SMRA demonstrated relatively more stable performance, supported by its township development business model and contributions from recurring income. The research findings indicate that differences in business models are a key factor influencing the magnitude of the impact of PSAK 115 implementation on the financial performance of real estate companies.